Mentoring Assistant Professors: Supporting and Nurturing Talent Needed to Grow a Program - Jeffrey Zacharakis (Adult Education Research Conference, 2024)
This paper provides an overview of a land grant university's college of education assistant professor mentoring program, and how mentoring is needed to develop successful junior faculty and grow an academic program in a neoliberal environment.
Keywords: Mentoring; Faculty Development; Program Development